Exploring Customer Loyalty and Experience Quality in VOD Netflix: The Role of Currency in Conversation and Co-Creation - Khairuna, Dina Wafiq; Bintarti, Surya (Jurnal Manajemen, 2024)
In addition to harming the movie industry, the impact of the COVID-19 pandemic has also increased the number of internet users. People spend a lot of time at home causing boredom, to overcome this, they fill their free time with various activities such as watching their favorite movies on digital platforms. This media is called a video on demand (VOD) service platform. The purpose of this study was to test Currency moderates Conversation and Co-Creation on Customer Loyalty with the mediation of Experience Quality in the Netflix application. The number of respondents in this study were 113 respondents who had used the Netflix VoD application. This study shows the results that all variable values in the reliability test used use Cronsbach’s alpha or composite reliability. This research proves that the conversation activities carried out by Netflix can drive the level of experience quality. Co-creation provided by Netflix can encourage the level of experience quality. The currency offered by Netflix can moderate the conversation but has a weak role in the level of experience quality. The currency set by Netflix can moderate the conversation towards the level of experience quality. Experience quality felt by Netflix consumers can affect the level of customer loyalty. Experience quality felt by consumers when using Netflix services can mediate conversation but has a weak role in the level of customer loyalty. Experience quality felt by consumers in using Netflix services can mediate co-creation but has a weak role in the level of customer loyalty.